Beyond aspirations: deploying the capability approach to tackle the under-representation in higher education of young people from deprived communities. Issue 2 (4th May 2017) - Campbell, Laurie Anne; McKendrick, John H.
ABSTRACT: This paper re-examines the low participation of young people from deprived communities through the lens of the capability approach. A fundamental problem for tackling widening participation is that much of the thinking of policymakers is grounded on the flawed 'poverty of aspiration thesis'. This paper contends that Sen's [1992. Inequality Re-Examined . Oxford: Clarendon Press; 1999. Development as Freedom . 1st ed. New York: Oxford University Press] capability approach offers a better way of theorising and understanding the persistent under-representation in higher education of young people from deprived communities. A comparative case study approach was conducted in two secondary schools in Scotland, each serving a deprived area, each of which has an intervention programme that promotes higher education. The study employed mixed methods (i.e. questionnaires and interviews) to investigate young people's aspirations and perceptions of their capabilities. The findings confirm findings from previous studies that are critical of the 'poverty of aspirations' thesis, which suggest that young people have high aspirations. However, an understanding of this is enriched when appraised within the framework of the capability approach, as aspirations are rationalised against findings, which demonstrate that these same young people are also confident in their capabilities and that social arrangements are instrumental in supporting capability development.